The model of management of Vietnamese Public Universities in the context of contemporary global world conditions = Model zarządzania wietnamską uczelnią publiczną w kontekście współczesnych uwarunkowań globalnych - Khoa, Dinh Xuan; Hung, Pham Minh (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study and proposal of the model of public university management in Vietnam in the era of socialist-oriented market economy and international globalization are issues of both theoretical and practical significance. This corresponds to the need for a fundamental and comprehensive renewal of higher education in the current era in Vietnam.
Keywords: szkolnictwo wyższe; zarządzanie uczelnią publiczną; model zarządzania uczelnią; publiczna uczelnia wyższa; higher education; public university management; university management model; public university